An evaluation of the neutrophil-to-lymphocyte ratio as a prognostic and predictive marker in thromboangiitis obliterans (Annals of Medical Research, 2021)
None
Keywords: Thromboangiitis Obliterans; Neutrophil-To-Lymphocyte Ratio; Predictive Marker; Prognostic Marker.